Efficacy and Safety of Bevacizumab Biosimilar FKB238 Versus Originator Bevacizumab: Results from AVANA, a Phase III Trial in Patients with Non-Squamous Non-Small-Cell Lung Cancer (non-sq-NSCLC) - Syrigos, Konstantinos (BioDrugs, 2021)
BACKGROUND: Bevacizumab is an antiangiogenic recombinant humanized monoclonal antibody that inhibits tumor growth. FKB238, a bevacizumab biosimilar, has analytical pharmacokinetic and safety profiles similar to those of bevacizumab. OBJECTIVE: This phase III trial (NCT02810457) compared the efficacy and safety of FKB238 with that of bevacizumab in patients with advanced/recurrent non-squamous non-small-cell lung cancer (non-sq-NSCLC). METHODS: This global, multicenter, double-blind, parallel, randomized, comparative clinical trial enrolled and randomized patients with advanced/recurrent non-sq-NSCLC to receive intravenous infusions of either FKB238 15 mg/kg or bevacizumab 15 mg/kg. All patients received intravenous infusions of paclitaxel 200 mg/m(2) and carboplatin (area under the curve 6.0) immediately prior to investigational products for 4–6 cycles. FKB238 and bevacizumab were administered on day 1 of each 21-day cycle until objective progressive disease by RECIST version 1.1 or other discontinuation criteria were met. The primary efficacy endpoint was overall response rate (ORR), including complete and partial response and based on blinded independent central review assessment. Other efficacy determinations included progression-free survival (PFS), overall survival (OS), and immunogenicity. Adverse events and severity were reported. RESULTS: The ORR for the intent-to-treat (ITT) population (N = 731) was 51.6% in the FKB238 arm (N = 364) and 53.7% in the bevacizumab arm (N = 367). The FKB238:bevacizumab ORR ratio (ITT population) was 0.96 (90% confidence interval [CI] 0.86–1.08), and the difference in ORR (per-protocol set) between FKB238 and bevacizumab was − 0.02 (95% CI − 0.09 to 0.06). Both CIs fell within the prespecified equivalence margins. Estimated median PFS was 7.72 and 7.62 months in the FKB238 and bevacizumab arms, respectively (hazard ratio 0.97; 95% CI 0.82–1.16). Treatment-emergent adverse events (TEAEs) were reported for 94.2% and 95.1% of patients in the FKB238 and bevacizumab arms, respectively. Grade 3 or higher TEAEs were reported for 53.6% and 55.5% of patients in the FKB238 and bevacizumab arms, respectively. Serious TEAEs were reported for 25.1% and 26.0% of patients treated with FKB238 and bevacizumab, respectively. CONCLUSIONS: Efficacy equivalence was demonstrated between the two drugs, and safety profiles were similar. There were no meaningful differences in efficacy and safety between FKB238 or bevacizumab in patients with non-sq-NSCLC. TRIAL REGISTRATION NUMBER: NCT02810457.